Effect of rice bran and carboxymethyl cellulose addition on the physicochemical quality of chicken sausage formulated with red palm mid fraction - Alina A.R.; Siti Mashitoh A.; Abdul Salam B.; Maznah I.; Muhyiddin Y.; Syamsul K.M.W. (2024)
Indexed by Scopus